2020
DOI: 10.1155/2020/4765809
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Inhibin B and Follicle-Stimulating Hormone (FSH) Level between Normal and Infertile Men in Yaoundé

Abstract: Objective. Hormones play a vital role in initiating and maintaining male reproductive function. The present study explores the influence and predictive ability of two reproductive hormones on semen quality among men who were partners in an infertile couple. Design. During our cross sectional study, men were recruited from private and public hospital and laboratories for clinical evaluation of fertility status. Methods. Fresh semen samples were assessed for quality (concentration, motility and morphology) accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…26 Supportive study was done by Mamiafo Corinne et al found a negative correlation between FSH and semen parameters in male partners of infertile couples. 27 A study conducted in 161 oligozoospermic men found normal level of LH and TST, but FSH levels show a negative association with sperm count which supports our findings. 28 Biswas et al found several fold higher concentrations of LH in seminal plasma when compare to serum and also found the concentration was lower in azoospermia compared to oligozoospermia and normozoospermia group.…”
Section: Discussionsupporting
confidence: 89%
“…26 Supportive study was done by Mamiafo Corinne et al found a negative correlation between FSH and semen parameters in male partners of infertile couples. 27 A study conducted in 161 oligozoospermic men found normal level of LH and TST, but FSH levels show a negative association with sperm count which supports our findings. 28 Biswas et al found several fold higher concentrations of LH in seminal plasma when compare to serum and also found the concentration was lower in azoospermia compared to oligozoospermia and normozoospermia group.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, MetS cases had a decrease of FSH, testosterone and inhibin B, while no significant difference was found in LH, estradiol, prolactin, and AMH. Previous studies reported a decrease of inhibin B and an increase of FSH in infertile males ( 37 ). However, our meta-analysis indicated a similar change trend of FSH and inhibin B in MetS.…”
Section: Discussionmentioning
confidence: 84%
“…FSH plays an important role in spermatogenesis. Clinical studies reported that FSH levels were higher in infertile patients compared with fertile controls, and that FSH was negatively correlated to sperm concentration in the population surveyed ( 22 ). However, the relationship between FSH and sperm morphology has been rarely reported.…”
Section: Discussionmentioning
confidence: 99%